Teaching strategies mediated by ICT. Last two decades in Colombia (Encuentros, 2021)
The paper takes up the results of the research project "Scientific and academic production in technology and informatics in Colombia: discourses and practices 2000 - 2018", in the teaching-learning category, to carry out a more reflective analysis. The behavior of the journals in the last three calls for measurement endorsed by Minciencias is presented, because the corpus of study is extracted from there. In didactic strategies, the largest number of articles were located, which account for the bets of Colombian and foreign researchers to mobilize ICTs from the pedagogical, didactic and educational, at school and university level. It is concluded that since technology and information technology was established in Law 115 of 1994, there are curious and creative teachers who have begun to test the available hardware and software resources with all the configurations and semantics that have been emerging with information technologies and communication.
Keywords: Learning - Teaching - Didactic strategies - ICT – technology